Mechanics of Biological Systems and Materials, Volume 6 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Tekalur, Srinivasan Arjun; Zavattieri, Pablo; Korach, Chad S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
5thInternational Symposium on the Mechanics of Biological Systems and Materials, Volume 6 of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the sixth volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range of areas, including:  Soft Tissues Mechanics Bio-Engineering and Biomechanics Natural Materials & Bio-Inspiration Novel Techniques and Experiments in Biomechanics Tissue Engineering Cells Mechanics.
From the Contents: Damage in Brain Tissue due to Single Bubble Cavitation Shock -- Inflation Test of the Human Optic Nerve Head Using Digital Volume Correlation -- In Situ NANO-indentation of Round Window Membrane -- Transient Response of the Eardrum Excited by Localized Mechanical Forces -- In Vitro Quantification of Optimal Impact Properties for Micro needle Penetration into Skin.
Keywords: Biomedical engineering; Biomaterials; Mechanics, Applied; Solids; Regenerative medicine; Biomedical Engineering and Bioengineering; Biomaterials; Solid Mechanics; Regenerative Medicine and Tissue Engineering